2022
DOI: 10.1042/bst20210281
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 and genetic screens in malaria parasites: small genomes, big impact

Abstract: The ∼30 Mb genomes of the Plasmodium parasites that cause malaria each encode ∼5000 genes, but the functions of the majority remain unknown. This is due to a paucity of functional annotation from sequence homology, which is compounded by low genetic tractability compared with many model organisms. In recent years technical breakthroughs have made forward and reverse genome-scale screens in Plasmodium possible. Furthermore, the adaptation of Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…This is in part due to the success of phenotypic approaches but also partly enforced by the lack of robustly validated drug targets in Plasmodium. However, the emergence of improved genetic tools for the study of this apicomplexan parasite has enabled many more viable drug targets to be identified and robustly validated. ,, This, coupled with the fact that the massive screening efforts of organizations such as Medicines for Malaria Venture has explored and now exhausted much of the available chemical space, has led to a renewed focus on target-based drug discovery. To support this decided change of emphasis, the development of additional tools and methodologies will be required.…”
Section: Discussionmentioning
confidence: 99%
“…This is in part due to the success of phenotypic approaches but also partly enforced by the lack of robustly validated drug targets in Plasmodium. However, the emergence of improved genetic tools for the study of this apicomplexan parasite has enabled many more viable drug targets to be identified and robustly validated. ,, This, coupled with the fact that the massive screening efforts of organizations such as Medicines for Malaria Venture has explored and now exhausted much of the available chemical space, has led to a renewed focus on target-based drug discovery. To support this decided change of emphasis, the development of additional tools and methodologies will be required.…”
Section: Discussionmentioning
confidence: 99%
“…However, they provide no data for the cellular location of individual proteins nor cell lines for their functional analysis. For instance, Zhang et al (2018) provides a predicted score of essentiality for P. falciparum genes that – despite its usefulness – does not preclude experimental validation for individual targets of interest (Ishizaki et al, 2022). These latter issues are solved by gene-by-gene screens that however typically lack through-put in malaria parasites (Ishizaki et al, 2022; de Koning-Ward et al, 2015; Rancati et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Zhang et al (2018) provides a predicted score of essentiality for P. falciparum genes that – despite its usefulness – does not preclude experimental validation for individual targets of interest (Ishizaki et al, 2022). These latter issues are solved by gene-by-gene screens that however typically lack through-put in malaria parasites (Ishizaki et al, 2022; de Koning-Ward et al, 2015; Rancati et al, 2018). Taking advantage of the selection-linked integration (SLI) system for genomic modification (Birnbaum et al, 2017) we here carried out a proof-of-concept study covering all unknown ‘non-secretory’ proteins (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed CRISPR/Cas9 gene editing technique was used to screen the PySRA knockout strain in vivo to further explore the specific regulation mechanism of PySRA on the host inflammatory response. The CRISPR/Cas9 technique comprises Cas9 endonuclease and guides RNA (gRNA), which helps Cas9 achieve specific recognition and cleavage of target sequence sites ( 37 39 ). In this study, no resistant strains were found after electroconversion and pyrimethamine screening.…”
Section: Discussionmentioning
confidence: 99%